2021
DOI: 10.5435/jaaosglobal-d-21-00006
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Pyoderma Gangrenosum After Outpatient Knee Arthroscopy

Abstract: Pyoderma gangrenosum is an immunologic, ulcerative cutaneous condition often associated with systemic disease and frequently precipitated by trauma. It is noninfectious, but the inflammatory assault can resemble a malignant infection such as necrotizing fasciitis. Despite its clinical resemblance to infection, surgical de ´bridement worsens the condition and may remove morphologic clues to the true disease, thus creating a vicious cycle of surgical de ´bridements and disease progression. Furthermore, diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In nearly all of the cases (33/34) described in these reports, the lesions worsened after debridement (Table ). 4,7,[17][18][19][20][21][22][23][24][25][26][27][39][40][41][42][43][44][45][46][47][48][49]51 In addition, 13 reports describe patients with PG on immunosuppressant medication who had lesions debrided and sometimes grafted. None of these patients had any reported worsening of their PG wounds (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In nearly all of the cases (33/34) described in these reports, the lesions worsened after debridement (Table ). 4,7,[17][18][19][20][21][22][23][24][25][26][27][39][40][41][42][43][44][45][46][47][48][49]51 In addition, 13 reports describe patients with PG on immunosuppressant medication who had lesions debrided and sometimes grafted. None of these patients had any reported worsening of their PG wounds (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Ebrad et al 19 conducted a review and found three cases of PG that occurred after THA 19. Also, a case has been reported where PG was seen after knee arthroscopy 20. Recently, Mizushima et al 21 described a patient with myelodysplastic syndrome who received granulocyte colony stimulating factor to prevent postoperative infections 21.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Also, a case has been reported where PG was seen after knee arthroscopy. 20 Recently, Mizushima et al 21 described a patient with myelodysplastic syndrome who received granulocyte colony stimulating factor to prevent postoperative infections. 21 The patient developed PG a few days after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…81 (Supplemental Digital Content 4, http://links.lww.com/PRSGO/C962.) Orthopedic Surgery PSPG manifested in six patients after total knee arthroplasty, 65,73,76 knee arthroscopy, 49 intramedullary nail osteosynthesis, 64 or internal fixation. 65 (Supplemental Digital Content 5, http://links.lww.com/PRSGO/C963) One of the patients had a previous episode of PSPG.…”
Section: Dermatologic Surgerymentioning
confidence: 99%